Plasticity is a locally adapted trait with consequences for ecological dynamics in novel environments. Issue 16 (21st July 2021) - Bond, Matthew N.; Piertney, Stuart B.; Benton, Tim G.; Cameron, Tom C.
Abstract: Phenotypic plasticity is predicted to evolve in more variable environments, conferring an advantage on individual lifetime fitness. It is less clear what the potential consequences of that plasticity will have on ecological population dynamics. Here, we use an invertebrate model system to examine the effects of environmental variation (resource availability) on the evolution of phenotypic plasticity in two life history traits—age and size at maturation—in long‐running, experimental density‐dependent environments. Specifically, we then explore the feedback from evolution of life history plasticity to subsequent ecological dynamics in novel conditions. Plasticity in both traits initially declined in all microcosm environments, but then evolved increased plasticity for age‐at‐maturation, significantly so in more environmentally variable environments. We also demonstrate how plasticity affects ecological dynamics by creating founder populations of different plastic phenotypes into new microcosms that had either familiar or novel environments. Populations originating from periodically variable environments that had evolved greatest plasticity had lowest variability in population size when introduced to novel environments than those from constant or random environments. This suggests that while plasticity may be costly it can confer benefits by reducing the likelihood that offspring will experience low survival through competitive bottlenecks in variable environments. In this study, we demonstrate how plasticity evolves in response to environmental variation and can alter population dynamics—demonstrating an eco‐evolutionary feedback loop in a complex animal moderated by plasticity in growth. Abstract : Phenotypic plasticity is expected to evolve in variable environments, but the consequences this might have for population dynamics in a changing world are currently unknown. Here, we show that plasticity in life history traits can evolve which in turn modulates population dynamics in novel conditions. This evidences the potential role of plasticity in moderating eco‐evolutionary feedback loops.